EXPLORING THE CHALLENGES OF DIGITAL TEXTBOOKS IN READING COMPREHENSION - Ningsih, Ariyanti Abi; Weganofa, Riza; Mafulah, Siti (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
Reading is a crucial skill that contributes to the language, mind, social, and cultural development of students. In addition, in the digital era technology is widely found and can be used properly. Digital textbooks have become an inevitable part of leisure time, study assignments, and work duties, facilitating online learning and blended learning. But there are also individuals who reject the existence of new technology. This study highlights the challenges of digital textbooks in reading comprehension. This study utilized literature review research, which is a survey of scholarly sources on a specific topic. The researchers reviewed 24 articles published between 2018 and 2023 from ERIC Journal and Google Scholar, analyzing the content and information in the articles. The study found that digital textbooks can impact students' focus ability, as they can be easily distracted by social media, notifications, and web browsing. This could explain why paper-based media appears to favor reading comprehension in unsupervised settings where learners are less exposed to such distractions. The use of digital textbooks must be accompanied by information literacy from digital technology. Digital textbooks offer a new experience in reading, but they also present challenges in terms of social-economic status, focus ability, and information literacy.